2016
DOI: 10.18500/1817-3020-2016-16-4-218-227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hydrogen Bond on the IR-spectrum and Structure of Molecular Complex of Diamond Nanoparticles and DNA Bases

Abstract: доктор физико-математических наук, профессор кафедры информационной безопасности автоматизированных систем, Саратовский государственный технический университет имени Гагарина Ю. А.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this work, we consider a simple model system consisting of individual DNA nitrogenous bases (NBs) (guanine (G), adenine (A), cytosine (C), and thymine (T)). Besides one theoretical work of the authors of this article, we are not aware of experiments performed on the adsorption of NBs on the ND surface, whereas there is a wide array of experimental studies and theoretical calculations on the interactions of the individual NBs of DNA with carbon nanotubes, , the particles of graphite and graphene, as well as particles of graphene oxide …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we consider a simple model system consisting of individual DNA nitrogenous bases (NBs) (guanine (G), adenine (A), cytosine (C), and thymine (T)). Besides one theoretical work of the authors of this article, we are not aware of experiments performed on the adsorption of NBs on the ND surface, whereas there is a wide array of experimental studies and theoretical calculations on the interactions of the individual NBs of DNA with carbon nanotubes, , the particles of graphite and graphene, as well as particles of graphene oxide …”
Section: Introductionmentioning
confidence: 99%
“…It is known that hydrogen bonds play an important role in interactions of ND surface groups with the surrounding molecules. ,− Detonation nanodiamonds (DNDs) dispersed in water weaken hydrogen bonds in water. Moreover, the influence of DNDs on the strength of hydrogen bonds in the solvent essentially depends on the surface functionalization of DND. , It was also found that in its turn, the optical properties of DND depend on the strength of hydrogen bonds of the surface groups of DND with the surrounding solvent molecules. Specifically, the stronger the hydrogen bonding between surface functional groups of DND and solvent molecules, the weaker the intrinsic fluorescent properties of DND. These facts make it possible to consider DND as an efficient nanoagent in the biological tissue when using them as sensors or adsorbents of DNA.…”
Section: Introductionmentioning
confidence: 99%